Determinants of Audit Fees for Companies Listed on the London Stock Exchange - Chen, Xingli (2013)
This paper intends to examine the determinants of the level of audit fees in the UK audit market and to provide some up-to-date empirical evidence for previous literature. The empirical results are based on data of all non-financial companies listed on the London Stock Exchange in the five year period from 2008 to 2012. An audit fee model for the UK market is developed. Consistent with previous studies, findings show that normally used variables, such as the size, the complexity of auditee, and audit risk all have an important impact on the audit fees paid by UK clients. Less employed variables, for example non-audit services fees and industry specialisation, are also indicating a significant effect. Moreover, Big firm premium is clearly found in the total sample, thereby performing further test to see whether or not internal differences existed among the Big 4 accounting firms.